Proteinase-activated receptors (PARs) as targets for antiplatelet therapy. (11th April 2016) - Cunningham, Margaret; McIntosh, Kathryn; Bushell, Trevor; Sloan, Graeme; Plevin, Robin
Abstract : Since the identification of the proteinase-activated receptor (PAR) family as mediators of serine protease activity in the 1990s, there has been tremendous progress in the elucidation of their pathophysiological roles. The development of drugs that target PARs has been the focus of many laboratories for the potential treatment of thrombosis, cancer and other inflammatory diseases. Understanding the mechanisms of PAR activation and G protein signalling pathways evoked in response to the growing list of endogenous proteases has yielded great insight into receptor regulation at the molecular level. This has led to the development of new selective modulators of PAR activity, particularly PAR1. The mixed success of targeting PARs has been best exemplified in the context of inhibiting PAR1 as a new antiplatelet therapy. The development of the competitive PAR1 antagonist, vorapaxar (Zontivity), has clearly shown the value in targeting PAR1 in acute coronary syndrome (ACS); however the severity of associated bleeding with this drug has limited its use in the clinic. Due to the efficacy of thrombin acting via PAR1, strategies to selectively inhibit specific PAR1-mediated G protein signalling pathways or to target the second thrombin platelet receptor, PAR4, are being devised. The rationale behind these alternative approaches is to bias downstream thrombin activity via PARs to allow for inhibition of pro-thrombotic pathways but maintain other pathways that may preserve haemostatic balance and improve bleeding profiles for widespread clinical use. This review summarizes the structural determinants that regulate PARs and the modulators of PAR activity developed to date.